A branched‐chain amino acid‐based metabolic score can predict liver fat in children and adolescents with severe obesity. Issue 4 (14th October 2020) - Lischka, Julia; Schanzer, Andrea; Hojreh, Azadeh; Ba Ssalamah, Ahmed; Item, Chike Bellarmine; de Gier, Charlotte; Walleczek, Nina‐Katharina; Metz, Thomas F.; Jakober, Ivana; Greber‐Platzer, Susanne; Zeyda, Maximilian
Summary: Background: Eighty percent of adolescents with severe obesity suffer from non‐alcoholic fatty liver disease (NAFLD). Non‐invasive prediction models have been tested in adults, however, they performed poorly in paediatric populations. Objective: This study aimed to investigate novel biomarkers for NAFLD and to develop a score that predicts liver fat in youth with severe obesity. Methods: From a population with a BMI >97th percentile aged 9‐19 years ( n = 68), clinically thoroughly characterized including MRI‐derived proton density fat fraction (MRI‐PDFF), amino acids and acylcarnitines were measured by HPLC‐MS. Results: In children with NAFLD, higher levels of plasma branched‐chain amino acids (BCAA) were determined. BCAAs correlated with MRI‐PDFF ( R = 0.46, p < .01). We identified a linear regression model adjusted for age, sex and pubertal stage consisting of BCAAs, ALT, GGT, ferritin and insulin that predicted MRI‐PDFF ( R = 0.75, p < .01). ROC analysis of this model revealed AUCs of 0.85, 0.85 and 0.92 for the detection of any, moderate and severe steatosis, respectively, thus markedly outperforming previously published scores. Conclusion: BCAAs could be an important link between obesity and other metabolic pathways. A BCAA‐based metabolic score can predict steatosis grade in high‐risk children and adolescents and may provide a feasible alternative to sophisticated methods like MRI or biopsy in the future.